1997
DOI: 10.1046/j.1365-2141.1997.1442963.x
|View full text |Cite
|
Sign up to set email alerts
|

Types and sources of fuels for platelets in a medium containing minimal added fuels and a low carryover plasma

Abstract: Summary. The storage of platelets in synthetic media can result in plasma savings and reduced transfusion reactions. Accordingly, a wide range of storage formulations have been developed with the aim of replacing at least a proportion of the plasma in the storage medium. However, the concentrations and types of fuels in the carryover plasma, and the utilization of these fuels by platelets in storage, has not been investigated. We have developed a system which can measure total ATP turnover, and the contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The XF DMEM media used in these experiments did not contain free fatty acids. The source of fatty acids for oxidative phosphorylation is likely derived from endogenous free fatty acids and triglycerides stores that release fatty acids upon lipase activity [ 47 , 48 ]. It is important to note that fatty acid oxidation also occurs in the peroxisomes and with enzymes such as cyclooxygenase [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The XF DMEM media used in these experiments did not contain free fatty acids. The source of fatty acids for oxidative phosphorylation is likely derived from endogenous free fatty acids and triglycerides stores that release fatty acids upon lipase activity [ 47 , 48 ]. It is important to note that fatty acid oxidation also occurs in the peroxisomes and with enzymes such as cyclooxygenase [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we surmise that partial dysfunction of the poor PLT mitochondria will certainly play a role. As known for a long time, PLTs use glucose as the main fuel, but several other substrates such as amino acids and fatty acids may be used as well. The latter substrates depend on oxidative steps taking place in the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…36 There is a substantial amount of controversy regarding whether residual glucose must be present to maintain PLT viability during storage. 37,38 Our recent extensive storage studies evaluating apheresis PLTs stored in Plasmalyte have also indicated that the storage bag is critically important for maintaining PLT viability during storage in Plasmalyte. 36 For example, Rock and coworkers 22 obtained excellent poststorage results with PLTs stored in a polyolefin bag.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have been able to store Haemonetics‐collected apheresis PLTs for 13 days in Plasmalyte with poststorage PLT viability that meets FDA guidelines, and these PLTs have no residual glucose 36 . There is a substantial amount of controversy regarding whether residual glucose must be present to maintain PLT viability during storage 37,38 . Our recent extensive storage studies evaluating apheresis PLTs stored in Plasmalyte have also indicated that the storage bag is critically important for maintaining PLT viability during storage in Plasmalyte 36 .…”
Section: Discussionmentioning
confidence: 99%